Formulasi Pangan Flakes dengan Substitusi Tepung Kentang dan Tepung Wijen sebagai Alternatif Makanan Selingan Bagi Ibu Hamil - Lailia Wahyuliana; Annis Catur Adi (Universitas Batanghari Jambi, 2023)
The purposes of thisis studying was to analyzes the effectk off flakes food formulation as an alternative snack with substitutes for potato flour and sesame flour on acceptability, nutritional value rich in vitamin B6, high in energy, and low in fat, as well as economic value for pregnant women who experience morning sickness. Quasi-experimental research with a completely randomized research design. The number of panelists is limited, namely 3 people and untrained panelists, namely 25 people. Data collection included organoleptic tests based on characteristics (texture, aroma, color, and taste) and preference, product nutritional content (energy, fat, and vitamin B6), and nutritional economic value of the product. The data analysis used was a different test (Friedman Test) and an advanced test (Wilcoxon Signed Ranks Test). Substitution of potato flour and sesame flour on flakes texture (p = 0.000), flakes aroma (p = 0.002), flakes taste (p = 0.011), and flakes flavor with soy milk condiments (p = 0.025). Meanwhile, the color characteristics of flakes showed that there was no significant effect on flakes products (p = 0.095).